Karakteristik Tepung Suweg (Amorphophallus paeoniifolius) Termodifikasi Heat Moisture Treatment (HMT) Pada Produk Mie Kaya Serat - Indriany, Iin Trisni; ansharullah, ansharullah; Faradilla, RH Fitri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2019)
ABSTRACTThis research aimed to study the effect of temperature, heating time, the interaction between temperature and heating time on the physical characteristics of suweg flour, to study the absorption of water and the cooking power of suweg flour noodle modified by Heat Moisture Treatment (HMT). The design used in this study was factorial Complete Randomized Design with two factors. The first factor was the heating time (T) and the second was the heating temperature (S) which consisted of three levels namely 60ºC (S1), 70ºC (S2), 80ºC (S3) with a heating time of 5 hours (T1) and 8 hours (T2). Observation variables in this study were solubility analysis, swelling power, viscosity, noodle water absorption and cooking time, proximate (water, protein, carbohydrate, ash, fat and crude fiber), while organoleptic (color, aroma, texture and overall). Data from the results of physical analysis of flour and noodles were analyzed statistically using Analysis of Variance (ANOVA). The results showed that the heating time and the heating temperature had a very significant effect on swelling power, viscosity, and water absorption but did not affect solubility and cooking time. Selected flour based on the physical characteristics of flour and noodles was found in the treatment of T2S3 (the heating time of 8 hours at 80ºC) with swelling power 11.23 g/g, 25.47% solubility, viscosity 12.98cP, 157% noodles absorption and cooking time of 100 seconds. Proximate test results water 35.07%, protein 5,53%, ash 2,51 and fiber 14,37%. Organoleptic test result color 1.53 (dark brown), aroma 3.11 (slightly pungent), texture 3.15 (somewhat rubbery and overall were 2.90 (quite like). Based on the results of research, noodle products rich fiber meet SNI standards except protein levels.Keywords: suweg flour modified by HMT, characteristics of flour and wet noodles. ABSTRAKPenelitian ini bertujuan untuk mempelajari pengaruh suhu, lama pemanasan, interaksi antara suhu dan lama pemanasan terhadap karakteristik fisik tepung suweg, mempelajari daya serap air dan daya pemasakan mie tepung suweg termodifikasi HMT. Rancangan yang digunakan pada penelitian ini adalah rancangan acak lengkap (RAL) faktorial dengan dua faktor. Faktor pertama adalah lama pemanasan (T) dan kedua adalah suhu pemanasan (S) yang terdiri atas tiga taraf yaitu 60ºC (S1), 70ºC (S2), 80ºC (S3) dengan lama pemanasan 5 jam (T1) dan 8 jam (T2). Variabel pengamatan pada penelitian ini yaitu analisis solubilitas, swelling power, viskositas, daya serap air mie dan waktu pemasakan mie, proksimat (kadar air, protein, abu, dan serat kasar), sedangkan organoleptik (warna, aroma, tekstur dan keseluruhan). Data hasil analisis fisik tepung dan mie dianalisis secara statistik menggunakan Analysis of Varians (ANOVA). Hasil penelitian menunjukan lama pemanasan dan suhu pemanasan memberikan pengaruh sangat nyata terhadap swelling power, viskositas, dan daya serap air namun tidak berpengaruh terhadap solubilitas dan waktu pemasakan. Tepung terpilih berdasarkan karakteristik fisik tepung dan mie terdapat pada perlakuan T2S3 (lama pemanasan 8 jam dengan suhu 80ºC) dengan nilai swelling power 11,23 g/g, solubilitas 25,47 %, viskositas 12,98 cP, daya serap mie 157 % dan waktu pemasakan 100 detik. Hasil uji proksimat kadar air yaitu 35,07 %bb, protein 5,33 %bk, abu 2,51 % dan serat 14,37 %bk. Hasil penelitian organoleptik yaitu warna1,53 (coklat tua), aroma 3,11 (agak berbau tajam) tekstur 3,15 (agak kenyal) dan keseluruhan 2,90 (cukup suka). Berdasarkan hasil penelitian produk mie kaya serat telah memenuhi standar SNI terkecuali kadar protein.Kata kunci :Tepung suweg termodifikasi HMT, karakteristik tepung, mie basah.